2019
DOI: 10.1111/1462-2920.14596
|View full text |Cite
|
Sign up to set email alerts
|

Broad‐specificity GH131 β‐glucanases are a hallmark of fungi and oomycetes that colonize plants

Abstract: Summary Plant‐tissue‐colonizing fungi fine‐tune the deconstruction of plant‐cell walls (PCW) using different sets of enzymes according to their lifestyle. However, some of these enzymes are conserved among fungi with dissimilar lifestyles. We identified genes from Glycoside Hydrolase family GH131 as commonly expressed during plant‐tissue colonization by saprobic, pathogenic and symbiotic fungi. By searching all the publicly available genomes, we found that GH131‐coding genes were widely distributed in the Dika… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 73 publications
0
25
0
Order By: Relevance
“…The M . importuna SCYDJ1‐A1 genome possesses two copies of GH131 gene, a hallmark of plant‐tissue‐colonizing fungi (Anasontzis et al ., ), but none was likely expressed as an enzymatic protein during ENB decomposition, although their transcriptions were indeed observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The M . importuna SCYDJ1‐A1 genome possesses two copies of GH131 gene, a hallmark of plant‐tissue‐colonizing fungi (Anasontzis et al ., ), but none was likely expressed as an enzymatic protein during ENB decomposition, although their transcriptions were indeed observed.…”
Section: Discussionmentioning
confidence: 99%
“…The high transcription of chitin metabolism-related genes at day 15 might reflect early colonization of ENB by morel mycelium. The M. importuna SCYDJ1-A1 genome possesses two copies of GH131 gene, a hallmark of plant-tissue-colonizing fungi (Anasontzis et al, 2019), but none was likely expressed as an enzymatic protein during ENB decomposition, although their transcriptions were indeed observed.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that the symbiosisinduced ß-1,4-endoglucanase LbGH5-CBM1 from L. bicolor, acting on poplar cellulose, mannans and galactomannan, is involved in cell wall remodeling during formation of the Hartig net and this enzyme is required for successful symbiotic fungal colonization of poplar rootlets (Zhang et al, 2018). Also L. bicolor ß-glucanase GH131, active on polysaccharides with β-1,4, β-1,3, and mixed β-1,4/1,3 glucosidic linkages, is induced upon ectomycorrhiza formation (Anasontzis et al, 2019), further strengthening the concept of fungal PCWDEs as fundamental factors in the establishment of symbiotic plant-fungus interactions.…”
Section: Discussionmentioning
confidence: 79%
“…According to the identified proteins, it could be speculated that the exudates were involved in the formation of fungal cell walls, the growth of hyphae, and the formation of spores. Some of these proteins participated in the process of cell wall organization, including glucanases (KDB12613.1 and KDB14267.1) [31,32], glycosidases (KDB12546.1, KDB15368.1, and KDB13423.1) [33,34], mannoprotein (KDB10968.1) [35][36][37], and clock-controlled protein 6 (KDB12449.1) [38]. Glucans is an important component of the fungal cell wall, and is highly dynamic during cell wall morphogenesis.…”
Section: Discussionmentioning
confidence: 99%